Altitudinal specific variation in growing degree days of kiwifruit (Actinida chinensis) based on the BBCH scale - SHARMA, SUNNY; RANA, VISHAL SINGH (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2019–20 and 2020–21 at Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Himachal Pradesh aimed to apply easy-to-use mathematical equations for the temperature-based estimation of kiwifruit (Actinida chinensis var. deliciosa) cultivation’s Growing Degree Days (GDD) over the north-western Himalayan region. Five locations in three districts of Himachal Pradesh, namely Solan (Nauni and Kandaghat), Kullu (Bajaura and Seobagh), and Shimla (Phagli) were selected for the study. The experiment was laid out in a factorial randomized block design (F-RBD) with 10 treatments, and each treatment was replicated thrice. It is revealed that the highest average temperature was recorded at lower elevations. The earliest bud swell, bud break, open cluster, 50% visible petal, petal unfolding full bloom, and harvest maturity were observed at the Bajaura location during both years of study. A delay in the aforementioned phenophases of kiwifruit cultivars was noticed at higher elevations. The growing (GDD) was found to be highest in the Hayward cultivar at the Bajaura location. Fruit yields varied with climate (elevation) and cultivars. The Hayward performed better in terms of yield at higher elevations, unlike it was vice-versa in case of Allison.